Impact of macroeconomic surprises on carry trade activity - Michael Hutchison; Vladyslav Sushko (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
This paper investigates market perceptions of the risk of large exchange rate movements by using information gleaned from risk reversal contracts and macroeconomic news surprises. We focus on the height of the carry trade period in Japan (March 2004 through December 2006). Concerns about sharp yen appreciation were particularly evident during the period of heavy carry trade activity and are more likely to show up in the price of risk. We focus on 'big' news surprises that are more likely to convey information about the risk of large changes in the exchange rate, consider a broad set of news, and investigate the direct impact of news on the value of dollar yen risk reversals. We also consider the effect of the value of risk reversals on the yen carry trade, using (non-commercial) open interest positions in futures markets as a proxy for carry trade activity. Overall, we find that macroeconomic news is an important determinant of risk reversals during periods of heavy carry trade volume, particularly when the cost of hedging against large yen appreciation is increasing. Moreover, there is a close link between risk reversals and non-commercial futures positions. We calculate a substantial effect of macroeconomic news on carry trade activity, with risk reversals (the cost of hedging) as the transmission mechanism.
Keywords: C22; F31; G14; 330; Macroeconomic News; Risk Reversals; Foreign Exchange Futures; Carry Trade